Clinical and economic analysis of the use of the medicinal product dapagliflozin in patients with chronic heart failure and type 2 diabetes mellitus - M. V. Zhuravleva; J. V. Gagarina; T. V. Marin (Сахарный диабет)
OBJECTIVE: Clinical and economic evaluation of using the dapagliflozin in addition to standard therapy for patients with CHF (Chronic Heart Failure) and concomitant type 2 DM (Diabetes mellitus).MATERIALS AND METHODS: All adult Russian patients with confirmed diagnosis of CVD and concomitant type 2 DM were considered as the target population. We evaluated the use of dapagliflozin in addition to standard therapy in comorbid patients with CHF and DM type 2 on the indicators of CC death, death from any cause of hospitalization due to CHF, emergency treatment due to CHF, as well as calculated the cost per life year saved and quality-adjusted life year (QALY) saved both when using standard therapy alone and in combination with dapagliflozin.RESULTS: The use of dapagliflozin in addition to standard therapy for the treatment of comorbid patients with CHF and DM 2 per cohort of 1,000 people will prevent an additional 1,3 and 10 years:CHD-related hospitalizations: 40, 99, 195, respectively;Emergency admissions due to CVD: 15, 38, 73 respectively;CC deaths: 9, 19, 25 respectively;Deaths from any cause: 10, 21, 19At the same time, the costs per one year of quality-adjusted life saved were 1,923,509 rubles during the first year, 1,102,680 rubles during the first 3 years, and 560,841 rubles for 10 years, which did not exceed the calculated value of the willingness-to-pay threshold — 3.14 million rubles, and allowed us to conclude that dapagliflozin is clinico-economically feasible in the studied patient population.CONCLUSION: The use of dapagliflozin in addition to standard therapy for the treatment of comorbid patients with CHF and type 2 diabetes is clinically and economically feasible, considering the cost per year of life saved, adjusted for quality of life.